2007
DOI: 10.1093/ajcn/85.2.465
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of food folates is 80% of that of folic acid

Abstract: The aggregate bioavailability of folates from fruit, vegetables, and liver is approximately 80% of that of folic acid. The consumption of a diet rich in food folate can improve the folate status of a population more efficiently than is generally assumed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(58 citation statements)
references
References 21 publications
1
57
0
Order By: Relevance
“…We did not account for the higher bioavailability of supplemental folic acid compared with natural folate. However, the difference in bioavailability may be considerably lower than previously appreciated (Winkels et al, 2007). Furthermore, recalculating folate intakes according to Suitor and Bailey (2000), that is, including naturally occurring folate plus 1.7 times the amount of supplementary folic acid, only affected Spearman correlation coefficients at the third decimal (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…We did not account for the higher bioavailability of supplemental folic acid compared with natural folate. However, the difference in bioavailability may be considerably lower than previously appreciated (Winkels et al, 2007). Furthermore, recalculating folate intakes according to Suitor and Bailey (2000), that is, including naturally occurring folate plus 1.7 times the amount of supplementary folic acid, only affected Spearman correlation coefficients at the third decimal (data not shown).…”
Section: Discussionmentioning
confidence: 79%
“…4 Latest findings in literature have reported higher bioavailability of folate in foods than previously was suggested. 31 Of interest is that the results also provide a plausible explanation for the relatively low occurrence of SB in Southern European countries where the Mediterranean diet is 10 Nevertheless, this association should be interpreted cautiously, and further studies are needed to substantiate this finding. The PCA and RRR methods have identified a comparable dietary pattern, which was labelled 'Mediterranean' as it was characterised by high intakes of fruits, vegetables, vegetable oils, legumes, fish, alcohol and cereal products and low intakes of potatoes and sweets.…”
Section: Discussionmentioning
confidence: 93%
“…Supplements of folic acid are nearly 100% bioavailable under fasting conditions (31), and a long-term controlled dietary study indicated that the bioavailability of folate in a typical mixed diet was no more than 50% relative to that in a formula diet (32). A recent study showed that bioavailability of food folate was 78% of that of folic acid according to an isotope (33). Most water-soluble vitamins, except vitamin C, bind to proteins or sugars in food, and the bioavailability of these forms is considered to be lower than that of the free forms (5).…”
Section: Discussionmentioning
confidence: 99%